Fascism in Europe, 1919-1945 - Morgan, Philip, 1948- (Routledge companions., 2003)
Elusive and controversial, fascism is still the object of interest and debate over fifty years after its defeat in the Second World War. This new introduction looks at recent scholarship and the continuing debates on its nature.